OPENING THE SECRETS: ABOUT THE CONFRONTATION BETWEEN GERMANY AND THE UNITED STATES IN MEXICO IN 1914-1918 - I. A. Sokov (MGIMO University Press, 2018)
Book review: Mills, W.B. Treacherous passage: Germany’s secret plot against the United States in Mexico during World War I Lincoln: Potomac Books, 2017. 226 р.The reviewed book is the study by the historian of W.B. Mills from the University of Nebraska Lincoln, who devoted to the study of the still little-studied question of the international relations during the Great War. Thanks to the present available archival sources in Europe and America, the author of the book restored the history of the confrontation between the secret services of Germany and the United States in Mexico, aimed at obtaining a military advantage in the European war. The main story is the description of two wartime episodes involving Mexican ships, which were fought for by diplomatic and trade representatives, as well as by German intelligence agencies, to use them as fuel tankers of German submarines engaged in Sea raiding in the Pacific Ocean and the Caribbean Sea. Besides, the author introduces the reader about the activities of the Germans to organize bases for their submarines near the coast of Mexico, training in its territory in the camps of German mercenaries and planning for a joint invasion with Mexicans into the United States.